Prepared Magnesium Oxide Nanoparticles as Potential Antibacterial Agents - Hayder Fadhil abbas; Bilal Najm Abdullah (Genius Journals, 2023)
This study explores the synthesis of magnesium oxide nanoparticles (MgO NPs) using the sol-gel method and investigates their potential as antibacterial agents. The X-ray diffraction analysis confirmed the formation of crystalline MgO NPs with an average crystallite size of approximately 18.5 nm. Fourier Transform Infrared Spectroscopy (FTIR) revealed the presence of characteristic functional groups of MgO, along with some impurities. Scanning Electron Microscopy (SEM) demonstrated the spherical shape and uniform aggregation rate of the MgO NPs, with average particle size 23.1 nm. To assess their antibacterial properties, the MgO NPs were evaluated against Staphylococcus aureus and Escherichia coli using the Agar Diffusion Assay. The results revealed significant antibacterial activity against Escherichia coli, with an inhibition zone diameter of 16 mm at a concentration of 1000 µg/ml. This strong activity against Escherichia coli may be attributed to the small particle size of the MgO NPs. The findings suggest that the synthesized MgO nanoparticles possess promising antibacterial properties, particularly against Escherichia coli. Further research and optimization are needed to explore their potential applications as effective antibacterial agents, offering a safe and efficient alternative to traditional antibiotics to combat bacterial infections and antimicrobial resistance challenges in various fields.
Keywords: NPs; sol-gel method; Staphylococcus aureus and Escherichia col